Formation and dissociation kinetics of the FC(O)OOO(O)CF, FS(O2)OOO(O2)SF and FC(O)OOO(O2)SF trioxides. A theoretical study - Badenes, Maria Paula (2014)
A SACM/CT study of the FC(O)O + FC(O)OO -> FC(O)OOO(O)CF, FS(O2)O + FS(O2)OO -> FS(O2)OOO(O2)SF, FC(O)OO + FS(O2)O -> FC(O)OOO(O2)SF and FC(O)O + FS(O2)OO -> FC(O)OOO(O2)SF recombination reactions and their reverse dissociation processes was performed. The electronic energy along the reaction pathways was calculated at the G3S(MP2)//B3LYP/6-311+G(3df) level of theory. The respective high pressure rate coefficients obtained at 298 K are 3.2 x10−12, 4.3 x10−13, 8.5 x10−13,1.1 x10−12 cm3 molecule−1 s−1. The first calculated value compares very well with the available experimental one. From the corresponding thermal dissociation rate coefficients, lifetimes of about 170 days, 4 days and 1 min are predicted for FC(O)OOO(O)CF, FC(O)OOO(O2)SF and FS(O2)OOO(O2)SF.